Rancang Bangun Mesin Parutan Kelapa Skala Rumah Tangga Dengan Kapasitas 10 kg/jam - Roki Alianda; Muhammad Halil; Een Tonadi (MAJALAH TEKNIK SIMES, 2022)
This study aims to design, manufacture and test a coconut grated machine with a capacity of 10 kg/hour. The research method used in this research is an empirical method, namely field observations (observations) then from literature sources and then applied in one dimensional modeling with planning that is realized in one real form in the form of designing a coconut grating machine. This design is a coconut grater machine using 750 watts of electricity with pulley and belt transmission elements, with a grater system using a grater knife using a screw system. The results of the grater work obtained an average grater process of 36.72 Kg/hour. The advantages and disadvantages of designing the grated coconut machine that has been produced are very low noise levels and negligible vibration, because this machine is equipped with a pulley as a successor to the power of the electric motor. The increase in motor temperature for 2 hours to 4 hours of operation, there is no increase in motor temperature. The rotation of the grated head is quite good, it's just that the grated coconut with the shell is not clean, so the grating operation must be adjusted to the size of the coconut. The machine is easy to carry and safe to use.